Functional Pyrimidinyl Pyrazolate Pt(II) Complexes: Role of Nitrogen Atom in Tuning the Solid‐State Stacking and Photophysics. (6th May 2019) - Ganesan, Paramaguru; Hung, Wen‐Yi; Tso, Jen‐Yung; Ko, Chang‐Lun; Wang, Tsai‐Hui; Chen, Po‐Ting; Hsu, Hsiu‐Fu; Liu, Shih‐Hung; Lee, Gene‐Hsiang; Chou, Pi‐Tai; Jen, Alex K.‐Y.; Chi, Yun
Abstract: Pt(II) metal complexes are known to exhibit strong solid‐state aggregation and are promising for realization of efficient emission in fabrication of organic light emitting diodes (OLED) with nondoped emitter layer. Four pyrimidine–pyrazolate based chelates, together with four isomeric Pt(II) metal complexes, namely: [Pt(pm2z)2 ], [Pt(tpm2z)2 ], [Pt(pm4z)2 ], and [Pt(tpm4z)2 ], are isolated and systematically investigated for their structure–property relationships for practical OLED applications. Detailed single molecular and aggregated structures are revealed by photophysical and mechanochromic measurements, grazing‐incidence X‐ray diffraction, and theoretical approaches. These results suggest that these Pt(II) emitters pack like a deck of playing cards under vacuum deposition, and their emission energy is not only affected by the single molecular designs, but notably influenced by their intermolecular packing interaction, i.e., Pt···Pt separations that are arranged in the order: [Pt(tpm4z)2 ] > [Pt(pm4z)2 ] > [Pt(tpm2z)2 ] > [Pt(pm2z)2 ]. Nondoped OLED with emission ranging from green to red are prepared, to which the best performances are recorded for [Pt(tpm2z)2 ], giving maximum external quantum efficiency (EQE) of 27.5% at 10 3 cd m −2, maximum luminance of 2.5 × 10 5 cd m −2 at 17 V, and with stable CIE x, y of (0.56, 0.44). Abstract : Nondoped organic light emitting diodes (OLED) devices with emission ranging from green to red are prepared using four Pt(II) complexes that exhibit strong solid‐state aggregation and horizontal aligned transition dipole moments, while their stacking characteristics also play a crucial role in manipulating the emission properties.